Didactic Design Of Material Cubes and Beams Volume Elementary School Students Class V - Kurniawan, Asep; Herman, Tatang (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This study aims to create a didactic design of learning based on students' learning obstacles on the material volume of cubes and beams. The participants of this research were conducted in the fifth grade of elementary school in Sumedang Regency with 42 students consisting of 17 male students and 25 female students. The method used is the DDR (Didactical Design Research) method with data collection techniques used through observation, interviews, and documentation. The instrument used is a written test instrument. Data were analyzed qualitatively to determine student Learning obstacle, then make hypothetical learning trajectories and pedagogical didactic anticipation. Learning obstacle are identified, namely obstacles related to multiplication and division in finding volume, understanding the concept of volume, and understanding the story in the concept of cubes and beams. The results of this research are the improvement and development of didactic designs in mathematics that have mathematical connections with cube and beam material in elementary schools. Learning activities are carried out using a variety of methods including lecture, demonstration, practice and training methods, as well as using modified learning media and also using smartboards. From the results of the study it can be concluded that this didactic design can make learning situations more active so as to minimize Learning obstacle and make students easier to understand the subject matter